NMR-based plant metabolomics protocols: a step-by-step guide - Ocampos, Fernanda M. M.; de Souza, Ana Julia B.; Ribeiro, Gabriel H.; Almeida, Luísa S.; Cônsolo, Nara R. B.; Colnago, Luiz Alberto (Frontiers in Natural Products, 2024)
Metabolomics is one of the ‘omics’ sciences that can reveal the metabolic phenotype of organisms. This capability makes it a valuable tool for plant investigation, as plants present a vast chemical diversity. From the analytical point of view, two main techniques are frequently used in metabolomics and are often complementary: Mass spectrometry (MS) and Nuclear Magnetic Resonance (NMR) spectroscopy. Here, we describe NMR and its applications in plant metabolomics. We start by contextualizing the research field to then explore study design, sample collection, sample preparation, NMR data acquisition, and data analysis, showing the key features for achieving quality and relevant results. Within these topics, the most common databases used for plant metabolites identification and assignments are listed, as these help to shorten the laborious task of metabolomics investigation of natural products. Concerning NMR parameters, we discuss the key pulse sequences, recommend acquisition parameters, and examine the data each sequence can provide. Similarly, we delve into data analysis, highlighting the most commonly used chemometric methods and how to achieve high-quality results. Therefore, this review aims to provide a comprehensive guide for NMR-based metabolomics analysis of plants.